Determinan Minat Beli Konsumen: Analisis Content Marketing, Brand Awareness, dan Lokasi Usaha UMKM Emkaje Konveksi dan Bordir Kota Kediri - Chikilin Presmitha; Ismayantika Dyah Puspasari; Dyah Ayu Paramitha (Pusat Riset dan Inovasi Nasional, 2026)
Indonesia's micro, small, and medium enterprise (MSME) sector continues to expand rapidly, a trend reinforced by widespread digital adoption among more than 221 million internet users nationwide. While this growth opens considerable opportunities, it simultaneously confronts business owners with the challenge of stimulating consumer purchase intention. This study examines how content marketing, brand awareness, and business location relate to purchase intention among customers of UMKM Emkaje Konveksi dan Bordir in Kediri City. A quantitative causal-associative design was employed through a cross-sectional survey involving 80 respondents selected via convenience sampling, with data gathered through a Google Form questionnaire built on a five-point Likert scale and examined using multiple linear regression in SPSS 25. The findings reveal a mixed pattern across the three predictors: content marketing alone failed to produce a meaningful effect (t = -0.030, sig. = 0.977), whereas brand awareness emerged as a strong positive predictor (t = 5.325, sig. = 0.000) alongside business location (t = 2.844, sig. = 0.006). When considered jointly, all three variables exerted a significant combined effect on purchase intention (F = 63.778, sig. = 0.000), accounting for 70.4% of its variance based on the Adjusted R² value. These results point to brand-building and locational accessibility as the priority levers for MSMEs seeking to strengthen their marketing strategy in a digitally driven marketplace